A newly developed grab sampling system for collecting stratospheric air over Antarctica - Hideyuki Honda; Shinji Morimoto; Hiromitsu Akiyama; Gen Hashida; Shuhji Aoki; Hirotaka Ui; Takakiyo Nakazawa; Nobuyuki Yajima; Takashi Yamanouchi (Antarctic Record, 1996)
In order to measure the concentrations of various minor constituents and their isotopic ratios in the stratosphere over Antarctica, a simple grab sampling system was newly developed. The sampling system was designed to be launched by a small number of personnel using a rubber balloon under severe experimental conditions. Special attention was paid to minimize the contamination of sample air, as well as to allow easy handling of the system. The sampler consisted mainly of a 15l sample container with electromagnetic and manual valves, control electronics for executing the air sampling procedures and sending the position and status information of the sampler to the ground station, batteries and a transmitter. All these parts were assembled in an aluminum frame gondola with a shock absorbing system for landing. The sampler was equipped with a turn-over mechanism of the gondola to minimize contamination from the gondola, as well as with a GPS receiver and a rawinsonde for its tracking. Total weight of the sampler was about 11kg. To receive, display and store the position and status data of the sampling system at the ground station, a simple data acquisition system with a portable receiver and a microcomputer was also developed. A new gas handling system was prepared to simplify the injection of He gas into the balloon. For air sampling experiments, three sampling systems were launched at Syowa Station (69°00′S, 39°35′E), Antarctica and then recovered on sea ice near the station on January 22 and 25,1996.